HĒ ALĒTHEIA ELEUTHERŌSEI: SEBUAH PEDEKATAN EKSEGETIS TERHADAP INJIL YOHANES 8:31-32 - Zulkifli Oddeng (Manna Rafflesia, 2025)
The essence of truth in the general conception is always depends on the value of objectivity, coherence, or utility. Specifically in Christianity, truth – which is called Alētheia – is not tied to these values, but is found in Jesus Christ himself. An exegetical approach to the text of the Gospel of John 8:31-32 describes the concept of the liberating Alētheia, namely the condition that is equated with knowing the truth and becoming a disciple of Jesus when someone remains in Jesus and His word. By placing the issue of sin as a crucial context, this liberating concept of truth also triggers a rethinking of the idea of cosmic Christology, especially that proposed by Joas Adiprasetya, who proposed the possibility of actualizing the Alētheia in non-Christian religions.